Analysis Of Public Sentiment On Tax Policy Of Voluntary Disclosure Program With Vader Approach - Anggraeni, Windi Ariesti; Roji, Fikri Fahru (International Economic Conference of Business and Accounting, 2024)
This research aims to analyze public sentiment towards the existence of the Voluntary Disclosure Program tax policy on social media. This research method focuses on descriptive qualitative using sentiment analysis method with VADER (Valence Aware Dictionary and Sentiment Reasoner) approach. Data collection is done by using Twitter API and tweets based on keywords to see public perceptions of tax policy. The results showed that the public's opinion on the Voluntary Disclosure Program is very diverse, which is appreciation, support, and criticism. There is a neutral sentiment of 20%, moderately positive 28%, positive 37%, moderately negative 10% and negative 5%. Positive sentiment in this case obtained a greater value than negative sentiment, which means that public sentiment on the Voluntary Disclosure Program policy is quite good.